Child growth: analysis of schoolchildren regarding teaching methodology and pandemic context (International Seven Journal of Health Research, 2023)
With the remission of the COVID-19 Pandemic, it is remarkable to observe the changes that the different socioeconomic, family and educational contexts have resulted in child growth in the post-pandemic scenario. In order to contribute to a better understanding of this context and to assist the management of education and health teams with children, the study contemplates a statistical analysis of the BMI of students aged two to ten years old regarding variables of teaching methodologies before and after the pandemic and their relationship with changes in growth. It was described that the type of public education correlates with a greater deviation of the participants from the adequate growth channel, analyzing the influence of the pandemic on the living conditions of the sample in question. In this way, professionals from the health and education teams can direct the necessary changes to promote improvements in the health and quality of life of the population.